Application of Autism-Friendly Concept in the Interior Design of Autism Self-Development and Therapy Center in Surakarta - Shafa Syauqi Amalan; Lu'lu' Purwaningrum (TAMA: Journal of Visual Arts, 2024)
The Autism Self-development and Therapy Center is a special service center for people with autism with the main focus on developing self-development and therapy activities as an intervention effort for people with autism. The comparison between the number of children with autism is not comparable with the availability of facilities. Judging from the environment and the physical aspect of the building, in terms of capacity, activity, and space requirements, many things need to be improved. One of the facilities that currently needs to be made available in Surakarta is a facility that accommodates self-development activities. Apart from that, there are still many facilities with poor building conditions, some interior elements, and even furniture that are dangerous and unsafe for autistic children. Design efforts that can be made include creating self-development and therapy facilities with an autism-friendly concept. The form of design application that will be used from this autism-friendly concept is adjusting the type, texture, and color of materials and furniture to suit the needs of autistic children by considering safety and comfort factors. Thus, the autism-friendly concept is currently the best solution to overcome problems in autism facilities in Surakarta. The design method used in this design is based on references by Ballast (1992), starting with the Programming, Data Analysis, Idea Development, and Design Method (Design Development) stages. Based on the design results from the discussion, it is hoped that the Autism Self-development and Therapy Center can be a solution to the problems of children with Autism disorders and provide positive output for each autistic child.